The First Century of the International Joint Commission - Clamen, Murray; Macfarlane, Daniel (Canadian History and Environment, 2020)
An essential introduction to, and overview of, the International Joint Commission and Canada-U.S. water relationships. The International Joint Commission oversees and protects the shared waters of Canada and the United States. Created by the Boundary Waters Treaty of 1909, it is one of the world's oldest international environmental bodies. A pioneering piece of transborder water governance, the IJC has been integral to the modern Canada-United States relationship. This is the definitive history of the International Joint Commission. Separating myth from reality and uncovering the historical evolution of the IJC from its inception to its present, this collection features an impressive interdisciplinary group of scholars and practitioners. Examining the many aspects of border waters from east to west The First Century of the International Joint Commission traces the three major periods of the IJC, detailing its early focus on water flow, its middle period of growth and increasing politicization, and its modern emphasis on ecosystems. Informative, detailed, and fascinating, The First Century of the International Joint Commission is essential reading for academics, contemporary policy makers, governments, and all those interested in sustainability, climate change, pollution, and resiliency along the Canada-US Border.